Association between socio demographic profile with factors contribute in the intention acceptance of traceability among producer and wholesaler in Malaysia - Saipul Jannah, Juliana Ritonga; Man, Norsida; Abd Latif, Ismail; Yusoff, Melissa Alina (International Journal of Agriculture, Forestry and Plantation, 2016)
Food safety is worldwide important and has great attention for the agenda which has been highlighted in Agro-food Policy of Malaysia. The food safety and quality is an increasingly important issue in this country. Various factors such as improper use of pesticides, physical contamination, microbiological contamination, heavy metal contamination and environment have caused many severe food related problems including diseases in the country. The present study has shown that the problem of food safety and quality is somewhat a matter of permanent concern. To provide safe food products to consumers, traceability is one of the important criteria to be emphasized. Traceability has become one of the important agenda because it contributes in producing safe food. In addition, its plays an important role because it enhances the transparency and safety of the food system (Opara and Mazaud, 2001). The aim of this paper is to clarify the relationship between socio demographic factors with awareness and knowledge of traceability. A total of 200 respondents were selected randomly from fresh producers and wholesalers. Descriptive and chi-square analysis were selected by using SPSS Version 21. The result shows that most of the respondents were male, Malay and aged between 41 to 50 years. Most of the respondents have secondary school for their level of education. Age and education level have significant relationship with factors contribute in the intention acceptance of traceability among producer in Malaysia. While income has significant relationship with factors contribute in the intention acceptance of traceability among wholesalers in Malaysia. Traceability requires Research and Development (R&D) attention and acceptance of traceability among producer and wholesaler for the encouragement and enhancement of the production of fresh products. Additionally, government department especially Department of Agriculture need to take action in term of ranchers' demographic study such as age, education level and income which will enable producers and wholesalers to increase level of intention acceptance of traceability among producers and wholesalers. Thus, this farming could enhance and improve the intention of the producers and wholesalers for the development of traceability.